Features and significance of compiling the Newly Collated and Annotated Catalog of the Buddhist Canon. Issue 2 (2nd April 2016) - Mei, He
ABSTRACT: The Newly Collated and Annotated Catalog of the Buddhist Canon endeavors to consolidate the various existing catalogs of the Chinese Buddhist canons into a comprehensive reference tool for readers and researchers. This digital project aims to display the relations of the Chinese Buddhist canons to one another and supplement those scriptures missing from previous editions. This paper seeks to present and expound upon the features of the Newly Collated and Annotated Catalog in four parts: the history of the collated editions and catalogs of the Buddhist Canon; four particular issues that arise with these past collations; the Newly Collated and Annotated Catalog 's approach to creating a comparative catalog; and the means by which this catalog will be classified and arranged.